Pengaruh Variabel Makroekonomi Terhadap Jumlah Penghimpunan Zakat Di Indonesia - Sheema Haseena Armina (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
Purpose this study analyzes the effect of the industrial production index, the dollar exchange rate, inflation and the BI 7DRR on the amount of zakat collection from January 2015 to December 2018to identify the potential of zakat to support alleviation in Indonesia. Methodology approach: This study uses a quantitative approach with a Vector Error Correction Model (VECM) data analysis technique with time-series data from Januari 2015 t0 December 2018. Findings: The results show that in short term causality, there is an effect between long-term and short-term between zakat as the dependent variable with inflation and the dollar exchange rate. However, there is no short-term causality effect between BI 7-DRR and IPI to the amount of zakat while the long-term causality effect, all independent variables have a significant effect to the dependent variable namely zakat. Implications: The integration of Islamic philanthropic institutions has the potential to channel aid and support to alleviate poverty. This study adds the IPI variable to interpret the GDP variable in analyzing its effect on zakat.